Efficiency enhancement of distributed power amplifier design for radio frequency communication systems / Huan Hui Yan - Huan, Hui Yan (2017)
In the field of radio frequency (RF) and microwave communication system, there is an endless demand on wideband frequency operation and the amount of research work in the area of Power Amplifiers (PA) has grown as well to solve all kinds of problems. For instance, wireless portable devices have become common used in our daily life, but we often face the problem of its battery drains easily. Hence, a good design of PA can play an important role to satisfy all sorts of stringent needs. This research presents two designs of broadband distributed power amplifiers (DPAs) with different approaches. The first DPA designed using Pseudomorphic (PM) and Gallium Nitride (Xie) based with high-electron-mobility transistor (HEMT) technology as the power devices with the novel integration of broadband impedance transformer at the drain line termination. Besides, it demonstrated significant good performance over the entire bandwidth from 100 MHz to 2.4 GHz with 10 W output power performances and reaches average 35% of efficiency in 30 dB flat gains across bandwidth measured. On the other hand, the second DPA design driven by 3-stage of 10 W GaN HEMT with the gate line adjustment network and drain line tapering implementation for overall efficiency enhancement. Experimental of the prototype demonstrated output power of 41 dBm, flat gain at 12 dB, and bandwidth covering 80 MHz to 2.0 GHz with power added efficiency (PAE) 45% under 28 V drain bias. These concepts were implemented and developed in Advanced Design System (ADS) to obtain simulations and ideal performance. The research contribution has delivered bandwidth-efficiency improvements on the conventional distributed amplifier (DA) topology, battery life extension, and lower cost that is compatible with two-way radios communication applications such as Software Defined Radio (SDR). After all, this study offers practical skills and industrial realization in RF and microwave communications systems.